Government Pension Fund Management Strategy In Facing The Financial Crisis - Yap, Nonni; Lestari, Emi (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The financial crisis poses a significant challenge to the management of government pension funds, which aim to ensure retirees’ welfare and the long-term sustainability of the financial system. This study analyzes government pension fund management strategies in facing financial crises, focusing on investment policies, portfolio diversification, and risk mitigation mechanisms. The research method employed is a qualitative approach through a literature review and secondary data analysis from financial reports and government policies related to pension funds. The findings indicate that effective strategies include diversifying investments into more stable assets, implementing strict risk management, and policy reforms to enhance pension fund sustainability. Additionally, government involvement in providing guarantees and adaptive regulations in response to economic conditions plays a crucial role in maintaining pension fund stability. This study provides recommendations for policymakers to strengthen transparency, improve fund management efficiency, and develop more flexible policies to address global economic dynamics. With the right strategies, government pension funds can remain sustainable and provide optimal benefits for retirees.